2017
DOI: 10.1017/s1751731116002810
|View full text |Cite
|
Sign up to set email alerts
|

Influence of barley grain particle size and treatment with citric acid on digestibility, ruminal fermentation and microbial protein synthesis in Holstein calves

Abstract: Chemical and physical treatments of barley grain increase ruminally resistant starch and can improve the rumen fermentation pattern. The objective of the present study was to evaluate the effects of chemical (addition of citric acid, CA) and physical (grinding to two different particle sizes, PS) treatment of barley grain on performance, rumen fermentation, microbial protein yield in the rumen and selected blood metabolites in growing calves. In all, 28 male Holstein calves (172 ± 5.1 kg initial BW) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 30 publications
(47 reference statements)
1
20
0
Order By: Relevance
“…The other probable mechanism may be related to increased blood insulin concentration in response to supplemented some individual FA which was reported previously in beef cows fed with polyunsaturated plant FA (44) . Furthermore, sparing effect of FA for amino acid and glucose could increase these metabolite concentrations in the blood (9) that consequently both glucose (45) and amino acids (46) had potential to increase blood insulin concentration. The young calves are highly sensitive to insulin similar to non-ruminants (47) , and long-term effect of insulin concentration in dairy calves on future insulin sensitivity status may be a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…The other probable mechanism may be related to increased blood insulin concentration in response to supplemented some individual FA which was reported previously in beef cows fed with polyunsaturated plant FA (44) . Furthermore, sparing effect of FA for amino acid and glucose could increase these metabolite concentrations in the blood (9) that consequently both glucose (45) and amino acids (46) had potential to increase blood insulin concentration. The young calves are highly sensitive to insulin similar to non-ruminants (47) , and long-term effect of insulin concentration in dairy calves on future insulin sensitivity status may be a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…A possible approach to reduce the fermentation rate of starch in the rumen would be to modify the cereal particle size (grinding size) included within the pellet, as it is well known that lambs can use the whole grain cereal efficiently (Ørskov and Fraser, 1975). Feed intake, rumen ecosystem and fermentation parameters can be affected by cereal particle size (Pérez-Torres et al, 2011;Gimeno et al, 2015a;Kazemi-Bonchenari et al, 2017), but to the authors' knowledge there are no studies integrating all this information in weaned lambs intensively fattened during short periods of time (less than 50 days) with CPD. Changing grinding size of grain may cause changes in the composition of ruminal microbiota, affecting the rate of fermentation and the formation of end-products, and then the composition of ruminal contents and digesta reaching the abomasum.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [ 3 ] reported that lower ruminal pH in the calves fed on BG depressed intake. Different particle size, [ 11 ] as well as starch availability rate [ 10 ] could influence ruminal pH. However, similar ruminal pH across experimental diets were observed in the current study, which was partly because GMPS was similar among experimental diets ( Table 1 ).…”
Section: Discussionmentioning
confidence: 52%
“…A linear decrease in ruminal NH 3 -N concentration in dairy cows was reported as a result of an increasing proportion of BG in the diet [ 9 ]. This may be related to the BG starch structure which is rapidly degradable and easier accessible for ruminal microbes [ 9 , 10 ]. DePeters and Fergusen [ 33 ] reported that BUN could be used as an indicator of ruminal N captures, as this value is positively associated with ruminal NH 3 -N concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation